Transcriptome analysis reveals key regulatory networks and genes involved in the acquisition of cold stress memory in pepper seedlings - Jian Li; Ping Yang; Hongbo Fu; Juan Li; Yanzhuang Wang; Keyan Zhu; Jihua Yu; Jie Li (BMC Plant Biology)
Abstract Temperature is an important limiting factor in the counter-seasonal cultivation of pepper. Currently, there are no studies on transcriptomic analysis of ‘cold stress memory’ in pepper. In this study, in order to understand the mechanism of ‘cold stress memory’ in pepper (Capsicum annuum L.), seedlings were subjected to the following treatments: normal temperature treatment (P0), the first cold treatment for 3 days (P3), the recovery temperature treatment for 3 days (R3), and another cold treatment for 3 days (RP3). The results showed that P3 plants wilted the most, RP3 the second and R3 the least. Leaf reactive oxygen species (ROS) and electrolyte leakage were the most in P3, the second in RP3 and the least in R3. In addition, RP3 had the highest accumulation of zeaxanthin, violaxanthin and β-cryptoxanthin, followed by P3, and R3 had the least. These results suggest that pepper seedlings are characterized by ‘cold stress memory’. Transcriptomics was used to analyze the key genes and transcription factors involved in the biosynthesis of zeaxanthin, violaxanthin and β-cryptoxanthin during the formation of ‘cold stress memory’. This study provides candidate genes and transcription factors for an in-depth study of the cold tolerance mechanism in pepper.